Pyrroles as Privileged Scaffolds in the Search for New Potential HIV Inhibitors - Maria da Conceição Avelino Dias Bianco; Debora Inacio Leite Firmino Marinho; Lucas Villas Boas Hoelz; Monica Macedo Bastos; Nubia Boechat (MDPI AG, 2021)
Acquired immunodeficiency syndrome (AIDS) is caused by human immunodeficiency virus (HIV) and remains a global health problem four decades after the report of its first case. Despite success in viral load suppression and the increase in patient survival due to combined antiretroviral therapy (cART), the development of new drugs has become imperative due to strains that have become resistant to antiretrovirals. In this context, there has been a continuous search for new anti-HIV agents based on several chemical scaffolds, including nitrogenated heterocyclic pyrrole rings, which have been included in several compounds with antiretroviral activity. Thus, this review aims to describe pyrrole-based compounds with anti-HIV activity as a new potential treatment against AIDS, covering the period between 2015 and 2020. Our research allowed us to conclude that pyrrole derivatives are still worth exploring, as they may provide highly active compounds targeting different steps of the HIV-1 replication cycle and act with an innovative mechanism.